Initial-Boundary Value Problem for Fractional Partial Differential Equations of Higher Order - Djumaklych Amanov; Allaberen Ashyralyev (Abstract and Applied Analysis)
The initial-boundary value problem for partial differential equations of higher-order involving the Caputo fractional derivative is studied. Theorems on existence and uniqueness of a solution and its continuous dependence on the initial data and on the right-hand side of the equation are established.